Pembuatan Alat Insinerator Ramah Lingkungan Penghasil Arang dan Asap Cair - Amirrianda, Rezky; Setiawan, Beny; Yusmita, Yesi; Azriadi, Emon; Fiatno, Aris (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Garbage or waste is a major problem currently happening, this problem has become a serious problem, especially in big cities, not only in Indonesia, but throughout the world. Many developed countries have made various efforts to overcome these problems, but have not had a significant impact. The purpose of this research is to: 1. Make an environmentally friendly incinerator that produces charcoal and liquid smoke. 2. Expected combustion results as planned. Data collection uses 2 ways, namely: 1. Direct observation, review and find out what is needed in the process of making incinerators. 2. Literature study, collecting relevant and appropriate data, by looking at previous research related to the manufacture of incinerators as waste burning devices. The conclusions of the study are: 1. The results of the manufacture of an incinerator using a drum capacity of 200 liters with a height specification of 0.98 meters and a width of 0.58 meters. 2. The results of physical testing of this incinerator are capable of producing charcoal and liquid smoke. 3. Testing the resistance of the incinerator from the heat generated by the combustion process is very good because the drum is coated with clay, while leakage at the top cover of the combustion chamber occurs because the gasket is not heat resistant.